2006
DOI: 10.1097/01.rlu.0000210526.50300.f7
|View full text |Cite
|
Sign up to set email alerts
|

F-18 FDG PET Demonstrates Crossed Cerebellar Diaschisis 20 Years After Stroke

Abstract: Stroke produces an area of focal damage and distant areas of reduced blood blow and metabolism termed diaschisis. Tc-99m ECD and HMPAO brain SPECT have demonstrated crossed cerebellar diaschisis (CCD) in patients with cerebral cortical infarct. SPECT findings reflect abnormal cerebral blood flow. CCD as shown on F-18 FDG PET reflects abnormal reflects glucose metabolism. We present the case of a patient with laryngeal cancer who also had a stroke in the left cerebral hemisphere involving the territory of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…However, acquired language impairment is not always associated with obvious focal damage. For example, in cerebellar diachisis, left frontal lesions result in functional changes and tissue loss in right cerebellar regions (Shih et al, 2006). These secondary lesion effects may not be visible by eye, but can be detected using automated methods that detect gray and white matter volumetric changes in high resolution images and the cumulative effects of these structural changes may potentially impact language recovery.…”
Section: Caveats and Future Directionsmentioning
confidence: 99%
“…However, acquired language impairment is not always associated with obvious focal damage. For example, in cerebellar diachisis, left frontal lesions result in functional changes and tissue loss in right cerebellar regions (Shih et al, 2006). These secondary lesion effects may not be visible by eye, but can be detected using automated methods that detect gray and white matter volumetric changes in high resolution images and the cumulative effects of these structural changes may potentially impact language recovery.…”
Section: Caveats and Future Directionsmentioning
confidence: 99%
“…14,15 While the original definition of CCD was based on the idea that it is a transient condition, 16 several publications have reported CCD up to decades after the index stroke. [17][18][19][20] Regarding the reversibility of CCD, however, several serial SPECT and PET studies demonstrated that some patients show complete reversal of CCD during follow-up. 11,13,[21][22][23] With respect to functional outcome, the majority of studies in stroke patients using SPECT or PET investigated subacute and chronic CCD, reflecting the fact that these imaging methods are not eligible to routinely assess perfusion in the acute stroke setting.…”
Section: Introductionmentioning
confidence: 99%
“…Brainstem lesions may produce cerebellar diaschisis, 9,10 which may last 20 years after stroke. 11 Although single photon emission computed tomography or positron emission tomography was not done in our patient, we infer that she had cerebellar dysfunction because of diaschisis. Cerebellar dysfunction may decrease human muscle tone and disturb human motor control.…”
Section: Discussionmentioning
confidence: 91%